2016
DOI: 10.1111/acer.13065
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake and Reduced Mortality in Patients with Traumatic Brain Injury

Abstract: Mortality rate due to TBI in the alcohol-intake group appears to be lower compared to that in the no-alcohol-intake group after adjusting for main confounding variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In our study, we found that there was significantly higher percentage of males in the alcohol-intake group than in the no-alcohol-intake group, consistent with data from prior studies showing that alcohol-induced injuries are more common in males than in females [ 9 , 11 , 12 , 18 , 19 ]. In the case of slips, our study showed that males were more likely to experience severe injuries than females (OR, 1.80; 95% CI, 1.72–1.87).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, we found that there was significantly higher percentage of males in the alcohol-intake group than in the no-alcohol-intake group, consistent with data from prior studies showing that alcohol-induced injuries are more common in males than in females [ 9 , 11 , 12 , 18 , 19 ]. In the case of slips, our study showed that males were more likely to experience severe injuries than females (OR, 1.80; 95% CI, 1.72–1.87).…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of patients who visited the clinic from 20:00 to 8:00 on the next day for the examination of blunt-force injuries was 77.7% among the alcohol-intake group, and 62% in the noalcohol-intake group. 11,12 While we did not examine the geographic locations where injuries occurred in our study, we hypothesize that if a patient who has consumed alcohol slips, this slip is likely to occur in a dark place, and patients are more likely to be discovered late in the night-time than at other times. Hundreds of diagnostic ICD-10 codes currently exist, making it difficult to individually identify the distribution of a particular code.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Notably, our COVID cohort was more likely to have CHF and be uninsured, both of which are known risk factors for mortality in trauma [26][27][28][29]. Additionally, COVID patients were less likely to be alcohol positive, though we doubt alcohol contributed to increased mortality as its relationship to mortality in trauma is controversial and some studies have even suggested it improves mortality [30][31][32][33][34][35][36]. Our COVID cohort also had a higher ISS and a higher percentage of patients with hypotension, though this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 87%